Dr. Elda Robb recieving citation and Honorary Alumna, 1955 - Duette (Tufts Archival Research Center, 2005)
8x10; from left to right: Miss Cockrell, Dean Kelley, Dr. Elba Robb, Mrs. Davies, Miss Eliot, President Wessell